(untitled) (FAVE Sección Ciencias Veterinarias, 2025)
The teaching of contemporary veterinary medicine demands innovative curricular designs that emphasize disciplinary integration. These designs enable students to build a strong foundation for their professional performance, supported by a teaching model that extends beyond the passive transmission of information. Instead, teachers actively guide and participate in the process of knowledge construction, utilizing an integrated teaching approach and an evaluation system focused on scientific and professional competencies and skills. This work presents an opinion about curricular integration, specifically through a proposal developed by faculty in Microbiology, Virology, and Infectious Diseases, aimed at informing discussions on a new curricular design at the FCV-UNCPBA. The proposal is structured around the concept of modular teaching and promotes interdisciplinary activities across courses within the Department of Animal Health and Preventive Medicine. This work is organized into several key components: an educational conceptual framework; guiding principles for the roles of teachers, students, and the learning environment; objectives; didactic design and its placement within the curricular map; the work and evaluation methodology; as well as the mechanisms for monitoring and assessing the expected impact of the proposal.